(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The family of Simaroubaceae is known to contain quassinoids and canthin-6-ones, secondary metabolites that have been reported to possess numerous biological activities such as anticancer. A biomimetic total synthesis of canthin-6-one using Pictet-Spengler condensation according to the procedure by Czerwinski et al. (2003) was explored. The aim of this study was to determine the viability of this reaction for structural modification. In this report, influential factors of carboxyl mediated Pictet-Spengler condensation reaction would be discussed.